The Influence of Transformational Leadership and Compensation on Employee Performance with Organizational Commitment as Mediation at Pelita Bangsa University - Septian Dwi Cahyo; Taufiq Rahman; Tri Ngudi Wiyatno (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
This research aims to determine the effect of transformational leadership and compensation on employee performance with organizational commitment as a mediating variable. This research was carried out at Pelita Bangsa University, Cikarang, Bekasi Regency, with the object being the employees who worked there. The population of this study was Pelita Bangsa employees with a sample of 117 respondents. This research is quantitative research using the SEM method and using the Lisrel 8.8 application as a data processing tool. This research shows that transformational Leadership has been proven to partially have no positive and significant effect on Employee Organizational Commitment. Compensation can partially has a positive and significant effect on employee Organizational Commitment. Partial Transformational Leadership have a positive and significant effect on employee performance. Compensation partially have a positive and significant effect on employee performance at Pelita Bangsa University.. Organizational Commitment can partially have a positive and significant effect on employee performance at Pelita Bangsa University. Organizational commitment in this research is a full mediating variable, because it mediates the variables of transformational leadership and compensation on performance